Development Of Music Aptitude Test Instruments For The Student Of Music Education Departement (Universitas Negeri Semarang, 2022)
It is necessary to develop a music aptitude test instrument as students, basic music knowledge is not optimally developed yet. Due to the inavailability of such instruments in the music education department, this study saimed to design and develop music aptitude test. The tests in used to measure students skills in understanding basic musical skills. This study used experimental quantitative approach. The findings resulted in 40 test items covering 8 teaching goals and 35 indicators aligned to the Semester Learning Plan (RPS) of solfeggio class. Further, the future research will focus on music aptitude test in audio form for the students.